THE PROBLEM OF CORRUPTION AND BRIBERY IN FINANCIAL AND CREDIT-BANKING INSTITUTIONS OF UKRAINIAN PROVINCES OF THE RUSSIAN EMPIRE IN THE SECOND HALF OF THE 19TH – BEGINNING OF THE 20TH CENTURY - Бурилов, Костянтин (SWorldJournal, 2024)
The article examines specific cases of corruption phenomena and financial fraud among owners of credit and banking institutions and state officials. It is emphasized that the study of interpersonal relationships in created corruption schemes is a new issu